Existe vida além do código binário? Os hackers e o redimensionamento de princípios modernos em práticas pós-modernas na sociedade informacional - Albuquerque, Mônica Ramalho de (2009)
After the development of new information and communication technologies in the twentieth century, new social and aesthetic phenomena emerged by the adaptation of cultural, political and economic elements reestablishment. The hacker s and their actions are an unfolding of this scenario and they are part of the computer underground. This study seeks to understand the influence of new information and communication technologies in social relations, the emergence of new subjects and elements of identification that are represented here by the hackers. Thus, it is necessary to make a theoretical discussion about the development of modernity and the post-modernity, considering post-industrial theory and following the relationship of science and technology in this discussion that turned to informational society. This implies to recognize the elements that form the cyberculture and counter activities and ideals of the hackers with aspects that show the instrumentation and information technology as a way to control knowledge and the dynamics of society today. Finally, we hope to identify through interviews that were conducted, the issues that structure the hacker s identity elements, their ideals, ethics and social practices.